Review on the advantages and disadvantages of cryptocurrency attacks / Najihah Rusli and Mohamad Fadli Zolkipli - Rusli, Najihah; Zolkipli, Mohamad Fadli (UiTM Cawangan Perlis, 2021)
The advantages and disadvantages of blockchain technology in cryptocurrency attacks will be explained in this article. Digital currency has been widely used around the world. The soaring value of digital currencies has also led to an increase in the use of cryptocurrency. Cryptocurrency is a form of payment that can be exchanged online for goods and services. The increasingly popular use of cryptocurrency around the world is causing criminals, and hackers are starting to attack cryptocurrency on an ongoing basis. With the advent of blockchain technology, it managed to save the digital currency system with the availability of a decentralized database. Each block has many transactions, and for new transactions will be recorded and added to a decentralized database with a cryptographic signature that does not change making it difficult for abuse and theft. The authors have examined the strengths and weaknesses of the blockchain in cryptocurrency attacks. As a result, the authors support that this blockchain technology can help deal with cryptocurrency attacks that occur.